Best Answer

You multiply 3 by x, and 3 by -2. Then you add everything together.

More answers

3x - 6

Q: How do you expand 3(x -2)?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x-2 and 2x-9, now for this it kind of depends on how the equation is set out if it set out likw this 3x-2+2x-9 then you would answer it like this: -6x+-18x= 12x

3(x plus 2) expanded --> 3x+6 Check out wolframalpha.com for more explanation (not advertising)

(3x - 5)5= (3x + -5)5= (5C0)(3x)5(-50)+(5C1)(3x)4(-5)1+(5C2)(3x)3(-5)2+(5C3)(3x)2(-5)3+(5C4)(3x)1(-5)4+(5C5)(3x)0(-5)5= (1)(243x5)(1)+(5)(81x4)(-5)+(10)(27x3)(25)+(10)(9x2)(-125)+(5)(3x)(625)+(1)(1)(-3125)= 243x5 - 2,025x4 + 6,750x3 - 11,250x2 + 9,375x - 3125

3x + 2 = 3x + 6 This is not possible.

-(3x -2) = 17 -3x + 2 = 17 - 3x = 15 x = -5

Related questions

3x-2 and 2x-9, now for this it kind of depends on how the equation is set out if it set out likw this 3x-2+2x-9 then you would answer it like this: -6x+-18x= 12x

3(x plus 2) expanded --> 3x+6 Check out wolframalpha.com for more explanation (not advertising)

8

(3x+4)(x-2) 3x2 -6x+4x-8 3x2-2x-8

x^2 + 3x + 2/(-3x) - x^2 - 2=3x-2+2/(-3x)=3x-2-2/(3x)

3(x plus 3) expanded --> 3x+9

9x2 + 12x + 4 = 9x2 + 6x + 6x + 4 = 3x(3x + 2) + 2(3x + 2) = (3x + 2)(3x + 2) = (3x + 2)2

If 2 divided by 3x it is equal to 2/3x

If you mean: 9x2+3x-2 = (3x+2)(3x-1) when factored

3x * (x - 4) = 3x*x - 3x*4 = 3x^2 - 12x.

3x * (x - 4) = 3x*x - 3x*4 = 3x^2 - 12x.

5=3x+2 3x+2-2=5-2 3x=3 ------ 3 x=1